Integrating biodiverse edible school practices: enriching undergraduate liberal education for elevated learning outcomes - Shen, Yuan Min; Sulaiman, Mazdida; Chen, Guan Lun; Weng, Hsiang Ching; Huang, Chong Ming; Jamaludin, Nazzatush Shimar; Kadir, Mohd Fakhrul Zamani (Frontiers in Education, 2025)
This study investigated the implementation of biodiverse edible school concepts in undergraduate liberal education courses across universities. It aims to evaluate the impact of integrating these concepts on students' learning outcomes related to biodiversity, agriculture, and sustainability. Teaching practices incorporating biodiverse edible school elements were developed and applied in six classes at National Taiwan University and one class at Universiti Malaya, covering various disciplines including agriculture, language, and green chemistry. Data were collected using classroom observations, assignments, and questionnaire surveys. The results showed that the interventions generally enhanced students' understanding of biodiversity and agriculture, increased their willingness to consume local and seasonal foods, and supported the achievement of course learning objectives. Outdoor educational activities were especially effective in improving students' knowledge of edible plants on campus. The findings contribute to experiential learning in agricultural and environmental education, offering practical examples for implementation in diverse educational contexts. Moreover, this study revealed that these practices aligned well with several Sustainable Development Goals, particularly Goal 2 (zero hunger), Goals 12 (responsible consumption and production), Goal 15 (life on land), and Goal 3 (good health and wellbeing). This study demonstrates that biodiverse edible school concepts can be successfully adapted for higher education, providing new ways to integrate these topics into university curricula.